An empirical study on integrating technology into statistics classroom practice - Ken W. Li (Journal of Pedagogical Research, 2022)
There has been much attention given to the use of technology in education; mostly concentrating on physical artifacts of technology to facilitate teaching delivery but little mentioning technology as a cultural resource to organize the learning environment promoting social interaction among students and between teacher and students. This paper thus attempts to derive a model of pedagogy in an IT environment taking social interaction in classroom learning into account and reports a process of validating the model through two observation studies and two questionnaire-based surveys.  The first observation study took place in a lecture theatre where a teacher led a class discussion toward developing statistical concepts and showed that all students were attentive and participative.  In the second observation study, the students in a computing laboratory were divided into small groups to solve statistical problems collaboratively.  The first survey was conducted during the term time to interview students through which they reported their personal perceptions of and attitudes toward the educational use of technology. A questionnaire in the second survey was sent to the students via e-mail after the term time. In the questionnaire, they were asked to compare the experience of working in an IT environment between the classrooms using and not using a model of pedagogy in an IT environment. The students in the surveys reported that teacher facilitation of group learning in the statistics module with technology were different from other statistics modules they took in the same academic year because they appreciated group discussion that promoted social interaction and fostered working relationships, thus leading to construction of knowledge. These four studies show consistent results and evidence in supporting a successful implementation of the model into a statistics classroom practice.  More importantly, the observation studies give a detailed account of peer collaboration, mutual assistance, and productive interaction in a process of discussion and the teacher sensitivity to adjust the means of scaffolding assistance that substantiate the survey findings.